Effects of Extreme Land Use Changes and Rainfall Types on Flood Process in Naoli River Basin - MA Ruixue; LIU Jianwei; PANG Xiaoteng (Renmin Zhujiang)
As the core grain-producing area of the Sanjiang Plain, the Naoli River Basin has undergone significant changes in land use structure over the past 40 years due to the implementation of agricultural restructuring and wetland restoration projects. Based on the characterization of historical rainfall changes in the Naoli River Basin, this paper establishes extreme land use scenarios and different rainfall scenarios and simulates and analyzes the response of flood processes in different return periods using the HEC-HMS model. The results are as follows. ① The multi-year average precipitation in the Naoli River Basin is 578.51 mm, with annual precipitation at each rainfall station showing a significant increasing trend. ② The HEC-HMS model demonstrates good simulation performance, with Nash values for all flood events during the calibration and validation periods over 0.85. ③ In the paddy field expansion scenario, the average change rates of peak flood flow and runoff depth are 61.45% and 61.05%, respectively, and the peak time is advanced by an average of 1.75 hours. In the dryland or wetland restoration scenarios, both peak flood flow and runoff depth are significantly reduced, with peak flood flow decreasing by 12.76% and 50.48%, respectively. The reduction effect of the wetland is more significant. Floods with shorter return periods are more sensitive to land use changes. ④ With the rainfall peak time delayed by 24 hours and the flood peak time postponed by 20 hours on average, the average growth rates of peak flood flow and runoff depth are 14.78% and 10.26%, respectively. The flood response under rainfall type I is more sensitive. When the rainfall center changes from the upstream area to the downstream area, the average change rates of the peak flood flow and runoff depth are -13.03% and -14.33% respectively, and the peak time is advanced by an average of 7.33 hours. The results can provide a scientific basis for water resource management and land use planning in the basin.